Psychological and somatic symptoms among breast cancer patients in four European countries - Roziner, Ilan (2022)
Funding: This project has received funding from the European Union's Horizon 2020 research and innovation program under grant agreement No 777167. Dr Kelada is supported by the Golda Meir Post‐Doctoral Fellowship Fund.